Maternal mental health after infant discharge: a quasi-experimental clinical trial of family integrated care versus family-centered care for preterm infants in U.S. NICUs - Linda S. Franck; Caryl L. Gay; Thomas J. Hoffmann; Rebecca M. Kriz; Robin Bisgaard; Diana M. Cormier; Priscilla Joe; Brittany Lothe; Yao Sun (BMC Pediatrics, 2023)
Abstract Background Involvement in caregiving and tailored support services may reduce the risk of mental health symptoms for mothers after their preterm infant’s neonatal intensive care unit (NICU) discharge. We aimed to compare Family-Centered Care (FCC) with mobile-enhanced Family-Integrated Care (mFICare) on post-discharge maternal mental health symptoms. Method This quasi-experimental study enrolled preterm infant (≤ 33 weeks)/parent dyads from three NICUs into sequential cohorts: FCC or mFICare. We analyzed post-discharge symptoms of perinatal post-traumatic stress disorder (PTSD) and depression using intention-to-treat and per protocol approaches. Results 178 mothers (89 FCC; 89 mFICare) completed measures. We found no main effect of group assignment. We found an interaction between group and stress, indicating fewer PTSD and depression symptoms among mothers who had higher NICU-related stress and received mFICare, compared with mothers who had high stress and received FCC (PTSD: interaction β=-1.18, 95% CI: -2.10, -0.26; depression: interaction β=-0.76, 95% CI: -1.53, 0.006). Per protocol analyses of mFICare components suggested fewer PTSD and depression symptoms among mothers who had higher NICU stress scores and participated in clinical team rounds and/or group classes, compared with mothers who had high stress and did not participate in rounds or classes. Conclusion Overall, post-discharge maternal mental health symptoms did not differ between the mFICare and FCC groups. However, for mothers with high levels of stress during the NICU stay, mFICare was associated with fewer post-discharge PTSD and depression symptoms.